Rancang Bangun Game Edukasi Math Whizzer Untuk Siswa UPTD SDN 08 Pemali - Anjelia, Nisvina; Azzahra Rahmanda, Iffah; Andriyanto, Sidhiq; Setya Pratama, Muhammad (Jurnal Inovasi Teknologi Terapan, 2025)
Mathematics learning is often considered difficult by elementary school students, which has an impact on their low interest and learning achievement. To overcome this problem, an Android-based educational game called "Math Whizzer" was developed to increase students' interest and understanding in learning mathematics. The development of this application uses the Rapid Application Development (RAD) method, which consists of four main stages. In the first stage, observations and interviews were conducted with teachers at UPTD SDN 08 Pemali, which revealed that monotonous learning methods made it difficult for students to understand the material. The second stage, system design, involved the use of Blender and Canva applications to design attractive interfaces and visual elements. The third stage, development, was carried out by building the application using Unity. The final stage, implementation, involved testing the application at UPTD SDN 08 Pemali. The test results showed that this application was very feasible to use in mathematics learning, with a percentage of eligibility from teachers of 97,1% and students of 92,4%. Testing by media and material experts showed that the application features functioned well, and the material was presented clearly and effectively. This application also improves students' understanding and interest in mathematics, as evidenced by the increase in the average posttest score to 82,3 compared to the previous pretest score of 51,3.